2020
DOI: 10.1002/pssb.202000331
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Response and Charge Redistribution Processes in GaAs/AlGaAs Multiple‐Quantum Wells Structure

Abstract: The impact of radiative and non‐radiative processes on the photovoltaic response of GaAs/AlGaAs multiple‐quantum wells is investigated by temperature, excitation power, and chopping‐frequency‐dependent surface photovoltage (SPV) measurements. It is shown that a systematic study of SPV amplitude along with phase spectra can provide important information on thermal escape, carrier localization, and spatial redistribution of charge carriers. Characteristic features in SPV‐phase spectra related to quantum well (QW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Kim et al [39] also explained the effect of carrier trapping at the defect states on the reduction of PR amplitude of InAs/GaAs quantum dots (QDs). In the surface photo-voltage (SPV) measurement, Haldar et al [40] reported the SPV phase delay in AlGaAs/GaAs multiple-QW structure due to the charge carrier localization at the heterointerfaces. This is also explained by the opposing electric field of the interface, which retard the drift of electrons under the surface electric field.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [39] also explained the effect of carrier trapping at the defect states on the reduction of PR amplitude of InAs/GaAs quantum dots (QDs). In the surface photo-voltage (SPV) measurement, Haldar et al [40] reported the SPV phase delay in AlGaAs/GaAs multiple-QW structure due to the charge carrier localization at the heterointerfaces. This is also explained by the opposing electric field of the interface, which retard the drift of electrons under the surface electric field.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, several researchers have studied the band structure of GaAs/GaAlAs. Subhomoy Haldar et al [18] have investigated, by thermal, excitation power, and chopping-frequency-dependent surface photovoltage (SPV) measurements, the role of radiative and non-radiative processes on the photovoltaic response of GaAs/AlGaAs multiple quantum wells. These measurements provide important informations on thermal escape, carrier localization and spatial redistribution of charge carriers.…”
Section: Introductionmentioning
confidence: 99%